Isolation and Determination of Hypericins from Different Parts of Hypericum triquetrifolium Turra Grown in Khozestan by UV/Visible Spectrophotometry - Nasrin Aghel; Zahra Ramezani; Haniyeh Jalalitalab (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background & Objective: Hypericin is a naphtodianthrone with multiple pharmacologic actions. Hypericum triquetrifolium Turra grows in different part of Iran. The aim of the present study was to isolate and determine the quantity of hypericins in different parts (leaf, flower and stem) of this plant grown in Khozestan province.Matrials & Methods: Different parts of Hypericum triquetrifolium Turra (leaf, flower and stem) were collected and extracted with methanol 50% using soxhlet apparatus. Hypericin was determined using UV/Visible spectrophotometer at 590 nm.Results: The percents of hypericin in leaves, flowers and stems were 310, 210 and 150 mg/100g, respectively.Conclusion: Leaves and flowers of Hypericum triquetrifolium Turra have considerable amounts of hypericin.